Wheat response to increase levels of Urea fertilizer (Baghdad Science Journal, 2009)
Pots experiment was conducted in the green house of Biology Department, College of Education ( Ibn-AL-Haithum), University of Baghdad , during the growing season of 2005-2006 , to study the effect of five levels of urea fertilizer (0,50,100,150and 200) mg/pot in on vegetative growth of one wheat cultivar (Adanania) upon randomized complete block design with four replications. The results showed that significant difference between urea fertilizer levels above in vegetative growth characteristics ( plant height , leaf area , chlorophyll content, dry matter weight , relative efficiency and relative yield ) It was also showed that 200 mg/pot level was superior to urea fertilizer levels others in above characteristics studied except relative yield .